A little history of archaeology - Fagan, Brian M. (Little histories, 2018)
"The thrilling history of archaeological adventure, with tales of danger, debate, audacious explorers, and astonishing discoveries around the globe. What is archaeology? The word may bring to mind images of golden pharaohs and lost civilizations, or Neanderthal skulls and Ice Age cave art. Archaeology is all of these, but also far more: the only science to encompass the entire span of human history--more than three million years! This Little History tells the riveting stories of some of the great archaeologists and their amazing discoveries around the globe: ancient Egyptian tombs, Mayan ruins, the first colonial settlements at Jamestown, mysterious Stonehenge, the incredibly preserved Pompeii, and many, many more. In forty brief, exciting chapters, the book recounts archaeology's development from its eighteenth-century origins to its twenty-first-century technological advances, including remote sensing capabilities and satellite imagery techniques that have revolutionized the field. Shining light on the most intriguing events in the history of the field, this absolutely up-to-date book illuminates archaeology's controversies, discoveries, heroes and scoundrels, global sites, and newest methods for curious readers of every age."--provided by Amazon.com.